Role of Yoga Therapy in Prevention of Tuberculosis in People Living with HIV Infection: Protocol for A Randomized Controlled Trial - Chauhan, Arohi; Chandrasekaran, Ambalam; Kondal, Dimple; Sinha, Abhinav; Prabhakaran, Dorairaj (National Journal of Community Medicine, 2023)
Background: TB is a common opportunistic infection (OI) among people living with Human Immunodeficiency Virus (PLHIV). PLHIV often resort to the use of traditional and complementary medicine (T&CM) to supplement ART in order to maintain and improve their health. Yoga therapy has vast potential and beneficial effects on lungs. This study will assess the proportion of PLHIV developing TB in intervention group as compared to the control group. The secondary objective is to assess the improvement in CD4 T cell count, development of other OIs and to explore the socio-behavioural factors affecting the adherence to yoga programme and ART. Methods: We propose a hospital-based RCT comparing the yoga group with usual care control group using quantitative methods for 3 years. A total of 1800 PLHIVs will be studied with 1:2 intervention to control group ratio. Each participant will be involved for 24 months (intervention delivery/follow-up). PLHIV in the intervention group will be given yoga therapy training of 45- minute duration once a month for 3-months followed by self-practice at home. Independent t tests and Z test for proportion will be used to compare the two groups at baseline. Intention to treat analyses will be conducted with participants as originally allocated at randomization to avoid bias. Alpha level will be set at 5%, using two-tailed for all inferences. Discussion: This study will generate preliminary data about effect of yoga on TB and other opportunistic infections as well as the feasibility and utility of further RCT in the domain. Trial Registration: ISRCTN74208821